2007
DOI: 10.1369/jhc.7a7209.2007
|View full text |Cite
|
Sign up to set email alerts
|

Familial Breast/Ovarian Cancer and BRCA1/2 Genetic Screening: The Role of Immunohistochemistry as an Additional Method in the Selection of Patients

Abstract: S U M M A R Y Only 20-25% of families screened for BRCA1/2 mutations are found positive. Because only a positive result is informative, we studied the role of BRCA1/2 immunohistochemistry as an additional method for patient selection. From 53 high-risk-affected probands, 18 (34%) had available paraffin blocks of their tumors and were selected for this study. Mutation screening was done by conformation-sensitive gel electrophoresis and multiplex ligation-dependent probe amplification. For immunohistochemistry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 43 publications
2
12
0
2
Order By: Relevance
“…However, we could not find similar association between loss of expression and mutation in BRCA 2 gene. This data is in concordance with similar results previously shown by other authors …”
Section: Discussionsupporting
confidence: 94%
“…However, we could not find similar association between loss of expression and mutation in BRCA 2 gene. This data is in concordance with similar results previously shown by other authors …”
Section: Discussionsupporting
confidence: 94%
“…A study evaluating IHC expression and mutational status of BRCA1 in HGOSC reported that IHC was an accurate and highly reproducible method for detecting germ line, somatic, or epigenetic mechanisms of BRCA1 loss. These findings were consistent with results from other studies examining the use of BRCA1 IHC (Byrne et al 2000, Vaz et al 2007, Garg et al 2013). …”
Section: Brca Immunohistochemistrysupporting
confidence: 92%
“…Recently, investigators have described tight associations between the loss of BRCA1 expression and relatively improved survival, although genetic analyses were not performed (1416). There is also a number of papers describing loss of BRCA1 expression in the setting of BRCA1 gene mutation (12, 17, 18). Kashima described loss of expression in 8 cases with BRCA1 germline mutation (12), while Skytte (17) reported a sensitivity of 80%, a specificity of 93%, and an estimated PPV of 73% based on having studied 15 “BRCA1 cancers.” In comparison, our study included significantly larger numbers of carcinomas lacking germline mutations and a detailed analysis of genetic abnormalities other than germline mutations.…”
Section: Discussionmentioning
confidence: 99%